Carotenoids in Fresh and Processed Food: Between Biosynthesis and Degradation - Crupi, Pasquale (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Carotenoids are uniquely functional polyene pigments that are ubiquitous in nature; aside from being responsible for the color of a wide variety of vegetables, interest has been focused on food carotenoids due to their likely health benefits. This Special Issue, "Carotenoids in Fresh and Processed Food: Between Biosynthesis and Degradation", consists of five peer-reviewed papers that cover a numerous new insights on the chemistry of carotenoids together with some observations related to their protection from photodegradation. Moreover, other considerations about their biosynthesis and influencing parameters in fresh food are included.